2020
DOI: 10.1016/s1470-2045(20)30310-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics, outcomes, and risk factors for mortality in patients with cancer and COVID-19 in Hubei, China: a multicentre, retrospective, cohort study

Abstract: Background Patients with cancer are a high-risk population in the COVID-19 pandemic. We aimed to describe clinical characteristics and outcomes of patients with cancer and COVID-19, and examined risk factors for mortality in this population. Methods We did a retrospective, multicentre, cohort study of 205 patients with laboratory-confirmed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and with a pathological diagnosis of a malignant tumour in nine hospitals within Hubei, China, from Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

57
712
21
25

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 531 publications
(850 citation statements)
references
References 25 publications
57
712
21
25
Order By: Relevance
“…A current report indicated the SARS-CoV-2 variant with Spike D614 to G614 increased the infectivity of the COVID-19. [19] However, the mortality of our study (6.7%) was much lower than that of general cancer patients (11.4-18.6%) [5,[8][9][10]. Besides, as to disease severity, 26.7% of breast cancer patients in our study had severe disease, which still lower than that of general cancer patients observed by H. Zhang (47.8%), Ma (54.1%), and Dai (34.3%) [7,8,20].…”
Section: Discussioncontrasting
confidence: 53%
See 4 more Smart Citations
“…A current report indicated the SARS-CoV-2 variant with Spike D614 to G614 increased the infectivity of the COVID-19. [19] However, the mortality of our study (6.7%) was much lower than that of general cancer patients (11.4-18.6%) [5,[8][9][10]. Besides, as to disease severity, 26.7% of breast cancer patients in our study had severe disease, which still lower than that of general cancer patients observed by H. Zhang (47.8%), Ma (54.1%), and Dai (34.3%) [7,8,20].…”
Section: Discussioncontrasting
confidence: 53%
“…As the most common cancer among women, breast cancer has a long treatment cycle resulting in immunosuppression and increased risk of infection [13], thus individuals with breast cancer are at increased risk of SARS-CoV-2 infection and should be given more attention. In our previous study, breast cancer patients had the highest proportion among all cancer patients with COVID-19 [9]. Their mortality rate was 14%, far below the average of general cancer patients (28%) [5,9].…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations